2019
DOI: 10.1097/md.0000000000016136
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine on treating chronic prostatitis/chronic pelvic pain syndrome

Abstract: Background: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common urinary system disease in the male population. Recent studies have shown that traditional Chinese medicine (TCM) can alleviate the pain caused by CP/CPPS to a certain extent and improve the quality of life of patients. In this systematic review, we aim to evaluate the effectiveness and safety of TCM for chronic prostatitis/chronic pelvic pain syndrome. Methods and analysis: We will search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 12 IL-2 is a regulatory growth factor that contributes to increased PGE-2 levels upon prostatitis, leading to microvasculature dilation, increased vascular permeability, and tissue edema. 13 MIP-2 and MIP-1α are chemotactic agents that recruit macrophages, lymphocytes and neutrophils to inflammatory sites. 14 Previous studies have shown that patients with chronic prostatitis have higher concentrations of MIP-2 and MIP-1α in their prostatic fluid, and that the levels of these cytokines are positively correlated with the severity of chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“… 12 IL-2 is a regulatory growth factor that contributes to increased PGE-2 levels upon prostatitis, leading to microvasculature dilation, increased vascular permeability, and tissue edema. 13 MIP-2 and MIP-1α are chemotactic agents that recruit macrophages, lymphocytes and neutrophils to inflammatory sites. 14 Previous studies have shown that patients with chronic prostatitis have higher concentrations of MIP-2 and MIP-1α in their prostatic fluid, and that the levels of these cytokines are positively correlated with the severity of chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been widely used in clinical trials of prostatitis in recent years (8). According to TCM, the cause of prostatitis is mainly in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment effects of these methods are not very satisfactory. Due to the multitargeted therapy and fewer side effects of traditional Chinese medicines (TCMs), there are more and more research studies that have focused on the prevention and treatment of CP with TCM [ 3 ]. Many TCM compound preparations and their active components such as Abacopteris penangiana [ 4 ], Bazhengsan [ 5 ], and flavonoids [ 6 ] were effective in the treatment of CP.…”
Section: Introductionmentioning
confidence: 99%